STUDY OF SEGREGATING NATURE IN LIQUID Al-Ga ALLOYS - Koirala, I; Singh, B P; Jha, I S (Scientific World, 2015)
We report energetic of mixing behavior of liquid Al-Ga alloys, using simple statistical theory through concentration dependence thermodynamic, structural, transport and surface properties at 1023K. The concentration dependent thermodynamic functions (free energy of mixing, enthalpy of mixing, entropy of mixing and activity coefficient of the component), structural functions (concentration fluctuation in the long wavelength limit and chemical short range order parameter), transport properties (diffusivity and viscosity) and surface properties (surface segregation and surface tension) have got special attention to show a tendency of homo-coordination of atom in the mixture. The theoretical analysis reveals that input parameter, order energy is temperature dependent and Al-Ga alloys is of weakly interacting system. Scientific World, Vol. 12, No. 12, September 2014, page 14-20